2018
DOI: 10.1039/c8cy00500a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic transfer hydrogenation of biomass-derived 5-hydroxymethylfurfural into 2,5-bis(hydroxymethyl)furan over tunable Zr-based bimetallic catalysts

Abstract: ZrBa-SBA is highly efficient for the MPV reduction of HMF to BHMF, as the etherification of BHMF was suppressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…However, strong Brønsted acid sites may cause side-reactions, such as the hydrolytic ring-opening to form levulinate products, especially at high reaction temperature. 28,61,65,71,72,74,75,92 Hence, a material constituted only by Brønsted acid sites should be effective for direct etherification to form product 7, being unable to activate the hydrogen transfer process. In contrast, hydrogen transfer by the MPV mechanism is favored over solid catalysts with a Lewis acid site and a neighboring base site.…”
Section: Influence Of the Catalyst Features On Activity And Selectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, strong Brønsted acid sites may cause side-reactions, such as the hydrolytic ring-opening to form levulinate products, especially at high reaction temperature. 28,61,65,71,72,74,75,92 Hence, a material constituted only by Brønsted acid sites should be effective for direct etherification to form product 7, being unable to activate the hydrogen transfer process. In contrast, hydrogen transfer by the MPV mechanism is favored over solid catalysts with a Lewis acid site and a neighboring base site.…”
Section: Influence Of the Catalyst Features On Activity And Selectivitymentioning
confidence: 99%
“…9 In a previous study, some of us reported that pure Lewis acid solids, such as Cu/SiO 2 prepared by a chemisorption-hydrolysis method, express limited activity in the CTH of furfural and low selectivity, due to ether formation, but catalysts with acid-base pairs, such as ZrO 2 , are definitely more active and selective. 51 In some cases, pure Lewis acidity accounts also for ether formation, 28,72,74 even though the mechanism is still poorly understood. 75,93 Catalysis Science & Technology Paper…”
Section: Influence Of the Catalyst Features On Activity And Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In bio‐refining, lignocellulosic biomass is deemed as a promising raw material that allows the production of a number of all‐purpose platform molecules, such as levulinic acid or 5‐hydroyxmethylfurfural (HMF), by chemical and/or biological routes . Particularly, HMF holds great promise to address numerous high volume markets for chemicals, materials, and fuels . For example, 2,5‐bishydroxymethylfuran (BHMF), synthesized by selective hydrogenation of HMF, is a versatile building block for the production of polyurethane foams, value‐added pharmaceuticals and bio‐based polymers …”
Section: Introductionmentioning
confidence: 99%
“…The employed metallic catalysts are typically expensive, with relatively harsh reaction conditions [20,25]. Likewise, transfer hydrogenation using alcohol (e.g., ethanol, 2-propanol) or formic acid as the liquid hydrogen source has also attracted much attention from many researchers [21,25,[29][30][31][32]. However, the use of formic acid may lead to the corrosion of the equipment and metal leaching, while the alcohol can further react with BHMF by etherification to reduce its selectivity [33].…”
Section: Introductionmentioning
confidence: 99%